2023
DOI: 10.3390/w15122245
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Reliability of Stationary Design Rainfall in a Mediterranean Region under a Changing Climate

Abstract: Extreme rainfall events have been more frequent in recent decades, potentially as a climate change effect. This has been leading to a higher risk of the failure of existing hydraulic infrastructures, and to a higher awareness regarding the unreliability of design rainfall calculated with reference to historical data recorded in the last century. With this in mind, the present study questions the stationary assumption of the rainfall Depth–Duration–Frequency curves commonly used in Sicily, the biggest island of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Rill erosion is formed due to flow concentration and is considered a transitional stage from surface erosion to rill and gully erosions [11,[16][17][18]. Generally, various rainfall characteristics, including intensity, duration, frequency, and erosivity [3,[19][20][21], hydraulic flow characteristics such as shear stress [22,23], depth and velocity [11,14,[24][25][26], as well as rill characteristics including depth, length, width, and density affect soil and water loss [11,14,27]. In this case, the behavior of rill development during successive rainfalls due to significant changes in soil components and its hydrological response is of considerable importance.…”
Section: Introductionmentioning
confidence: 99%
“…Rill erosion is formed due to flow concentration and is considered a transitional stage from surface erosion to rill and gully erosions [11,[16][17][18]. Generally, various rainfall characteristics, including intensity, duration, frequency, and erosivity [3,[19][20][21], hydraulic flow characteristics such as shear stress [22,23], depth and velocity [11,14,[24][25][26], as well as rill characteristics including depth, length, width, and density affect soil and water loss [11,14,27]. In this case, the behavior of rill development during successive rainfalls due to significant changes in soil components and its hydrological response is of considerable importance.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies 19 21 have examined the spatiotemporal patterns of rainfall in climatic zones across the world 22 25 . Some research has been conducted on the semi-regional scale of rainfall variability 26 29 . Throughout the past 100 years, the amount of rainfall on Earth has increased by around 2% 14 , but according to IPCC 30 , its growth has always been unequal in terms of time and space.…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al 35 observed for the annual average rainfall over the Tibetan Plateau in China, similar trends have been seen during the previous few decades, also the same pattern in India 33 , 36 , in northwest Pakistan 17 , 18 , and in the China-Pakistan Economic Corridor area 37 . However, the Yellow River Basin, China 38 , the Mediterranean region 29 , and Iran have all seen a decline in annual mean rainfall 19 . A significant upward trend in annual, monsoon, and pre-monsoon rainfalls has lately been found in Bangladesh, according to a growing number of earlier research 39 41 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation